A novel, ultrafast, ultrasensitive diagnosis platform for the detection of SARS‐COV‐2 using restriction endonuclease‐mediated reverse transcription multiple cross displacement amplification. Issue 2 (9th January 2023) - Huang, Junfei; Yang, Xinggui; Ren, Lijuan; Jiang, Weijia; Huang, Yan; Liu, Ying; Liu, Chunting; Chen, Xu; Li, Shijun
Abstract: Coronavirus disease 2019 (COVID‐19) is a highly infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‐COV‐2). Though many methods have been used for detecting SARS‐COV‐2, development of an ultrafast and highly sensitive detection strategy to screen and/or diagnose suspected cases in the population, especially early‐stage patients with low viral load, is significant for the prevention and treatment of COVID‐19. In this study, a novel restriction endonuclease‐mediated reverse transcription multiple cross displacement amplification (MCDA) combined with real‐time fluorescence analysis (rRT‐MCDA) was successfully established and performed to diagnose COVID‐19 infection (COVID‐19 rRT‐MCDA). Two sets of specific SARS‐COV‐2 rRT‐MCDA primers targeting opening reading frame 1a/b ( ORF1ab ) and nucleoprotein ( NP ) genes were designed and modified according to the reaction mechanism. The SARS‐COV‐2 rRT‐MCDA test was optimized and evaluated using various pathogens and clinical samples. The optimal reaction condition of SARS‐COV‐2 rRT‐MCDA assay was 65°C for 36 min. The SARS‐COV‐2 rRT‐MCDA limit of detection (LoD) was 6.8 copies per reaction. Meanwhile, the specificity of SARS‐COV‐2 rRT‐MCDA assay was 100%, and there was no cross‐reaction with nucleic acids of other pathogens. In addition, the whole detection process of SARS‐COV‐2 rRT‐MCDA, containing the RNA template processing (15 min) and real‐time amplification (36 min), can be accomplished within 1 h. The SARS‐COV‐2 rRT‐MCDA test established in the current report is a novel, ultrafast, ultrasensitive, and highly specific detection method, which can be performed as a valuable screening and/or diagnostic tool for COVID‐19 in clinical application.